Factores que intervienen en la cultura turística de los pobladores de la ciudad de Nauta 2023 - Guzman Paliza, Flor Angela (2025)
The purpose of this final report is to identify which factors intervene in the tourist culture of the residents of the City of Nauta 2023, in which we worked with an applied method, explanatory level with a non-experimental design, a sample of 366 was chosen. residents to whom a questionnaire was used to collect information. According to the results, it is shown that the influence of various factors on the tourist culture of Nauta is considerable, as demonstrated by the results of various linear regression tests where positive correlations are observed between geographical, historical, symbolic and tangible factors and local tourist culture. These factors together, each contributing in different proportions that vary from approximately 31% to around 46%, demonstrate that both tangible and historical elements as well as symbolic and geographical ones significantly influence how tourism is promoted and experienced in the region. location. The high statistical significance of each study reinforces the validity of these results, confirming that these elements are not only part of Nauta's identity, but also have a notable effect on attracting visitors and preserving the culture and traditions of the place.